The Influence Of Employee Competence And Work Dicipline On The Performance Of Employees In The Nosew Section Of PT Adis Dimension Footwear - Clara, Jesica Dhona; Fahmi, Khaerul; Setiawan, Temmy (Faculty of Science and Technology University of Pramita Indonesia, 2026)
This study aims to determine: (1) the partial effect of employee competence on employee performance; (2) the partial effect of work discipline on employee performance; (3) the simultaneous effect of employee competence and work discipline on employee performance.This study uses a quantitative descriptive method, which describes variables as they are, supported by numerical data generated from actual conditions. The population in this study was all production employees at PT. Adis Dimension Footwear Balaraja-Tangerang. The research sample consisted of 70 respondents. This study used a saturated sampling technique due to the small population size; therefore, the sample in this study used the entire population of 70 employees as respondents. Data collection techniques used were observation, questionnaires, and documentation. Data analysis used multiple linear regression analysis with SPSS 26. Data validity was obtained through a partial t-test and a simultaneous F-test.The results of this study indicate that (1) partially, employee competence significantly influences the t-test on the performance of No Sew employees at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value> t table (3.441>1.996) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (2) Partially, work discipline significantly influences the performance of No Sew employees at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value> t table (2.536>1.996) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (3) Simultaneously, workload and work environment significantly influence the performance of No Sew employees at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by F count> F table (12.720>3.13) with a significance level of 0.000. Thus Ha is accepted and H0 is rejected. Based on the research results, it can be concluded that employee competency and work discipline variables, both partially and simultaneously, have a significant influence on the performance of No Sew employees at PT. Adis Dimension Footwear Balaraja-Tangerang.